First record of Proprioseiopsis citri (Muma) (Acari: Phytoseiidae) from Brazil with a complementary description - Santos, Jandir C. [UNESP]; de Moraes, Gilberto J.; Demite, Peterson R. (Taylor & Francis, 2017)
Proprioseiopsis citri (Muma) (Acari: Phytoseiidae) is reported for the first time from Brazil. The specimens were collected from litter in Jaboticabal, State of São Paulo, Brazil. Measurements of holotype also are provided and the male is described for first time. A key to the species of Proprioseiopsis from Brazil is provided.
Keywords: Amblyseiinae; diversity; litter; Proprioseiopsina; taxonomy